Economic Fundamentals vs. Institutional Quality: Determinants of FDI Inflows in the Developing (D-6) Countries - Toni Prihandoko; Achmad Jufri (Jurnal Ekonomi Pembangunan, 2026)
This study investigates the macroeconomic and institutional determinants of Foreign Direct Investment (FDI) inflows within the Developing Six (D-6) countries, which consist of Indonesia, Malaysia, Pakistan, Turkey, Bangladesh, and Egypt. Utilizing a quantitative approach with secondary panel data spanning from 2012 to 2021, the research employs the Random Effect Model (REM) as the optimal estimation framework. The empirical findings reveal that fundamental economic variables, specifically the Exchange Rate and Gross Domestic Product (GDP), exert a positive and statistically significant influence on stimulating foreign capital inflows (ρ < 0.05). Regarding institutional quality, while political stability shows no significant impact (ρ > 0.05), the control of corruption is found to have a significant negative effect on FDI (ρ < 0.05). This suggests that in the D-6 context, higher levels of corruption control (higher scores) may paradoxically correlate with reduced FDI, or that investors prioritize market size and currency advantages over certain governance metrics. The study concludes that investor behavior in these nations is primarily driven by market-seeking motives, with economic fundamentals serving as the most dominant catalysts..